Chemical Characterization and Biological Study of Azadirachta indica Extracts - Jessinta, Sandanasamy; Azhari, H. Nour; Saiful Nizam, Tajuddin; Nour, A. H. (2014)
The utilization of the plant parts (bark, leaves and roots) of Azadirachta indica from Malaysia for research purpose were limited and most of the previous studies focused only on the leaves. Thus, this study focused on the volatile compounds and the cytotoxic study of crude and fractions obtained from bark, leaves and roots of A. indica. The analysis of the volatiles of the crude and fractions was performed via Gas Chromatography-Mass Spectrometry (GC-MS). The volatiles present vary according to the plant parts and extraction solvents. The bark aqueous fraction yielded highest amount of volatiles (19 compounds) that corresponds towards various reported activities. The n-hexadecanoic acid was the most frequently occurring compound detected in all extracts, bark (40.14 and 20.1%), leaf (65.18 and 44.79%) and root (20.55 and 9.14%) for crudes and fractions, respectively. Meanwhile, the cytotoxic bioassay against brine shrimp (Artemia salina) resulted that; the fractions were more toxic compared to the crude extracts. Among all the extracts, leaf ethyl acetate fraction provides a lethal concentration value (1.35 ± 0.40 ppm) of the lowest, followed by bark ethyl acetate (1.38 ± 0.33) and leaf chloroform fraction (2.14 ± 0.35 ppm) and thus indicating the highest cytotoxic effect. The bioassay proved that fractions provide a better extraction technique for the extraction of toxic phytochemicals compared to the crude extracts